2018
DOI: 10.18632/oncotarget.26438
|View full text |Cite
|
Sign up to set email alerts
|

The high-sensitivity modified Glasgow prognostic score is superior to the modified Glasgow prognostic score as a prognostic predictor for head and neck cancer

Abstract: BackgroundThere is increasing evidence that the inflammatory indices of modified Glasgow prognostic score (mGPS) and high-sensitivity mGPS (HS-mGPS) play important roles in predicting the survival in many cancer; however, evidence supporting such an association in head and neck cancer (HNC) is scarce.Materials and MethodsWe evaluated the impact of the mGPS and HS-mGPS on the overall survival (OS) in 129 patients with HNC treated at Aichi Cancer Center Central Hospital from 2012-2013. The mGPS was calculated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Their results suggested a serum CRP level of 0.3 mg/dL is a potentially significant threshold and improves the prognostic importance of the mGPS. The prognostic superiority of the Hs-mGPS over mGPS has been demonstrated in many series of nonurological malignancies such as neck and esophageal cancer [ 24 , 25 ]. For example, in 2020, Tao Hou et al reported that the Hs-mGPS was significantly associated with overall survival and disease-free survival in patients with soft-tissue sarcoma who underwent radical surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested a serum CRP level of 0.3 mg/dL is a potentially significant threshold and improves the prognostic importance of the mGPS. The prognostic superiority of the Hs-mGPS over mGPS has been demonstrated in many series of nonurological malignancies such as neck and esophageal cancer [ 24 , 25 ]. For example, in 2020, Tao Hou et al reported that the Hs-mGPS was significantly associated with overall survival and disease-free survival in patients with soft-tissue sarcoma who underwent radical surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hanai et al 25 reported that high-sensitivity mGPS (HS-mGPS) is effective in head and neck cancer areas. We plan to further investigate the prognostic factors of hypopharyngeal cancer by comparing mGPS with HS-mGPS in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mGPS is a composite of two common inflammatory biomarkers: CRP and albumin, both of which have individually been investigated in this analysis. The mGPS is validated for prognostication of relapse and increased mortality in different types of cancer [ 25 27 ], and can also predict clinical outcomes in patients with heart failure with preserved ejection fraction [ 28 ] While no studies to date have investigated its usefulness in COVID-19, we have demonstrated that mGPS is a potential tool for predicting risk of 28-day mortality. For a score of 2 vs. 1 or 0, we found an absolute increase of 26.3% (26.3% vs. 0.0%) mortality risk.…”
Section: Resultsmentioning
confidence: 99%